External noise level on lancaster PA474 - Trayford, R. S. (College of Aeronautics, 1963)
Measurements of the external noise level on the Lancaster aircraft PA474 were made at 10,000 feet at two flight speeds for various Merlin engine conditions. In addition the effect on the noise of running one of the Budworth gas turbines, used for the suction wing experiment, was determined. The results show that the maximum sound pressure level found in flight was 124 DB … [cont.].